A review of Cameroonian medicinal plants with potentials for the management of the COVID-19 pandemic - Fongnzossie Fedoung, E.; Biwole, A.B.; Nyangono Biyegue, C.F.; Ngansop Tounkam, M.; Akono Ntonga, P.; Nguiamba, V.P.; Essono, D.M.; Forbi Funwi, P.; Tonga, C.; Nguenang, G.M.; Kemeuze, V.; Sonwa, D.J.; et al. (Springer, 2023)
Since the outbreak in December 2019, in Wuhan (China) of COVID-19, approved drugs are still lacking and the world is seeking effective treatment. The purpose of this article is to review the medicinal plants with potential to be used as complementary therapies against COVID-19. Bibliographic information was searched in several databases (Google Scholar, PubMed, Scopus, ScienceDirect, PROTA, ResearchGate and GLOBEinMED), to retrieve relevant papers on (1) plants used to manage common symptoms of COVID-19, (2) plant secondary metabolites with confirmed inhibitory effects on COVID-19 and (3) plants exhibiting pharmacological activities of relevance for COVID-19 management. A total of 230 species was recorded as potential source of ingredients for the fight against the 2019 novel corona virus. Of these species, 30 contain confirmed antiCOVID-19 secondary metabolites, 90 are used traditionally to manage at least 3 common symptoms of COVID-19, 10 have immunostimulant activity, 52 have anti-inflamatory activity, 14 have antiviral properties and 78 species are documented as used to treat malaria. A PCA analysis showing cluster formatting among the recorded species indicates 4 groups of species and an array of possibility of using individual species or a combination of species for their complementary effects. The authors argue that Cameroonian medicinal plants can be of potential contribution to the fight against COVID-19. Further applied research is needed to provide more scientific evidence for their efficacy, to establish standard formulations and clinical studies as part of efforts to develop therapies for COVID-19.